Hepatitis B Virus Incidence and Risk Factors Among Human Immunodeficiency Virus-1 Negative Men Who Have Sex With Men in Kenya. (7th December 2016) - Wahome, Elizabeth; Ngetsa, Caroline; Mwambi, John; Gelderblom, Huub C.; Manyonyi, Gloria Omosa; Micheni, Murugi; Hassan, Amin; Price, Matt A.; Graham, Susan M.; Sanders, Eduard J.
Abstract: No data exist on hepatitis B virus (HBV) incidence among African men who have sex with men (MSM). We tested plasma samples archived between 2005 and 2014 for HBV core antibody or surface antigen seroconversion in a cohort of 312 initially human immunodeficiency virus (HIV)-1-negative MSM with no evidence of prior HBV infection. Hepatitis B virus incidence was 6.0/100 person-years (95% confidence interval [CI], 3.9–9.1). Hepatitis B virus acquisition was associated with being uncircumcised (adjusted incidence rate ratio [aIRR], 5.0; 95% CI, 1.5–16.8), recent HIV-1 acquisition (aIRR, 2.9; 95% CI, 1.1–7.7), rape (aIRR, 5.0; 95% CI, 1.2–20.4), and any tertiary education (aIRR, 3.2; 95% CI, 1.1–9.7). African MSM have a substantial risk of HBV acquisition and require vaccination urgently.